Analysis of characters in cartoons and fantasy animations within the scope of addiction and its effect on children - Sarman, Abdullah; Sarman, Emine (Journal of Dependence, 2022)
Cartoons known as children’s favorite programs, characters in fantastic animations are among the programs and characters that they experience continuously from the first days of their lives. Because children have fictional worlds and such content appeals to them. This causes them to enjoy listening to fairy tales, watching cartoons, and playing video games. Although the reasons for children to follow the characters in cartoons and fantasy animations are still debated, the common view is that children do not fully distinguish between fantastic situations and reality. Thinking that characters or heroes in fantasy animations are real can affect children’s belief in fantastic events, affecting the development, behavior and daily activities of young children. It is stated that problems that may arise can continue until adulthood when the necessary precautions are not taken by detecting them in the early period. In this review article, it is aimed to analyze the characters in cartoons and fantastic animations within the scope of addiction and to evaluate their effects on children within the scope of cognitive, physical, social and emotional development. It is aimed to integrate the data specified in the literature on the subject and to make some suggestions within the framework of the information obtained.
Keywords: Animation; cartoon; child; fantastic character